Vpliv amitriptilina in sertralina na kinetiko eksogenega histamina v krvi mačke v in vitro poskusih - Rajtar, Simona (Medicinski razgledi, 2004)
Histamine is a biogenic amine known as a primary mediator of allergic reactions. In brain, its role involves neurotransmission. Researches in the field of histamine pharmacokinetics have shown that antidepressants modify thepharmacokinetics of exogenous histamine in cats and rats. They decrease elevated histamine concentrations in plasma after an injection of exogenous histamine. Consequently, animals which have not been treated with antidepressants have significantly elevated histamine concentrations after an intravenous injection of this amine. In order to determine the extent to whichblood cells participate in the modification of exogenous histamine kinetics, in vitro tests were performed on cat blood. After taking blood samples, the plasma was separated from blood cells and exogenous histamine andtwo antidepressants, amitriptyline and sertraline, were added to the blood cells in vitro. The concentration of histamine in the samples was determined spectroflourometrically, while methylhistamine was determined using HPLC. The results indicate that both amitriptyline and sertraline in vitro increase the reuptake of exogenous histamine in cat blood cells, although the effect of sertraline is more significant than that of amitriptyline.
Keywords: Amitriptilin; Histamine Release; Drug Effects; Histamin; Histamin, sproščanje; Histamine; Blood; Kromatografija tekočinska; Kromatografija visokotlačna, tekočinska; Amitriptyline; Cats; Mačke; Chromatography, Liquid; Spektrometrija fluorescenčna; Chromatography, High Pressure Liquid; farmakokinetika; kri; Spectrometry, Fluorescence